PELAKSANAAN PERKAWINAN POLIGAMI PADA MASYARAKAT BATAK TOBA DI KECAMATAN RONGGUR NIHUTA KABUPATEN SAMOSIR PROVINSI SUMATERA UTARA - Simbolon, Tuppal Parasian; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Polygamy in the Batak Society in the past, before Christianity entered the Batak Land,polygamy or more than one wife were common problems. After Christianity replaced the religion ofthe Ancient Batak community, church rules strictly prohibited polygamy. The Samosir District,Longgur Nihuta sub-district, whose population is dominated by the Toba Batak tribe who areProtestant and Catholic, is still very thick with its customs. As happened in Ronggur NihutaSubdistrict, Salaon Dolok Village where there were several polygamous marriages carried out bythe Toba Batak indigenous people, so the authors were interested in raising the title